2009
DOI: 10.1371/journal.pgen.1000428
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a Bacterial Regulon Controlling Virulence and Mg2+ Homeostasis

Abstract: Related organisms typically rely on orthologous regulatory proteins to respond to a given signal. However, the extent to which (or even if) the targets of shared regulatory proteins are maintained across species has remained largely unknown. This question is of particular significance in bacteria due to the widespread effects of horizontal gene transfer. Here, we address this question by investigating the regulons controlled by the DNA-binding PhoP protein, which governs virulence and Mg2+ homeostasis in sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
156
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(162 citation statements)
references
References 73 publications
(93 reference statements)
4
156
2
Order By: Relevance
“…The presence of PhoP-binding motifs in the promoter region of the S. marcescens phoPQ operon allowed us to predict that the system would be autoregulated, as was previously determined for other bacteria, such as E. coli, S. enterica, and Y. pestis (39,62,68). To analyze the regulatory features of the PhoP/PhoQ system in Serratia, we obtained a phoP mutant using the suicide plasmid pKNOCK-Gm, and we also constructed a phoP::lacZ reporter transcriptional fusion as described in Materials and Methods.…”
Section: Features Of the Phop/phoq Regulatory System In S Marcescensmentioning
confidence: 74%
See 2 more Smart Citations
“…The presence of PhoP-binding motifs in the promoter region of the S. marcescens phoPQ operon allowed us to predict that the system would be autoregulated, as was previously determined for other bacteria, such as E. coli, S. enterica, and Y. pestis (39,62,68). To analyze the regulatory features of the PhoP/PhoQ system in Serratia, we obtained a phoP mutant using the suicide plasmid pKNOCK-Gm, and we also constructed a phoP::lacZ reporter transcriptional fusion as described in Materials and Methods.…”
Section: Features Of the Phop/phoq Regulatory System In S Marcescensmentioning
confidence: 74%
“…In the Serratia genus, the phoPQ ortholog has been previously identified in the Serratia proteomaculans 568 genome (62), and a search in the S. marcescens Db11 genome (http://www.sanger.ac.uk) also reveals a conserved phoPQ operon. S. marcescens PhoP exhibits 82% identity and 95% homology, while PhoQ exhibits 62% identity and 80% homology, to the Salmonella enterica PhoP and PhoQ proteins, respectively.…”
Section: Features Of the Phop/phoq Regulatory System In S Marcescensmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we found that growth in the presence of the ferrous iron chelator 2,2Ј-dipyridyl resulted in reduced expression of hilA-lacZ (data not shown). To rule out the possibility that 2,2Ј-dipyridyl may scavenge Mg 2ϩ from the cell, we assessed the effect of the chelator on the expression of a PhoP activated gene (pagP) using a pagP-lacZ fusion, where PhoP binds pagP and is essential for induction of this gene (4,52). Unlike with the hilA fusion, the expression of pagP-lacZ was not differentially affected by the addition of 200 M 2, 2Јdipyri-dyl to the growth media (see Fig.…”
Section: Vol 193 2011mentioning
confidence: 99%
“…Mg 2+ has been shown to be an important signal controlling gene regulation via the PhoPQ two-component regulatory system for a range of Gram-negative bacteria, including Y. pestis and Y. pseudotuberculosis (Grabenstein et al, 2004;Oyston et al, 2000). The PhoPQ regulon has been evaluated in Y. pestis and shown to involve over 400 differentially regulated genes (Grabenstein et al, 2006;Li et al, 2008;Perez et al, 2009;Zhou et al, 2005) including mgtB. However, the specific role of this transporter in these species and the contribution of MgtB to the phenotypes observed following inactivation of the PhoPQ regulon has not been studied.…”
Section: Introductionmentioning
confidence: 99%